Structural and protein interaction effects of hypertrophic and dilated cardiomyopathic mutations in alpha-tropomyosin - Chang, Audrey N.; Greenfield, Norma J.; Singh, Abhishek; Potter, James D.; Pinto, Jose R. (Frontiers in Physiology, 2014)
The potential alterations to structure and associations with thin filament proteins caused by the dilated cardiomyopathy (DCM) associated tropomyosin (Tm) mutants E40K and E54K, and the hypertrophic cardiomyopathy (HCM) associated Tm mutants E62Q and L185R, were investigated. In order to ascertain what the cause of the known functional effects may be, structural and protein-protein interaction studies were conducted utilizing actomyosin ATPase activity measurements and spectroscopy. In actomyosin ATPase measurements, both HCM mutants and the DCM mutant E54K caused increases in Ca2+-induced maximal activities, while E40K caused a decrease. Investigation of Tm’s ability to inhibit actomyosin ATPase in the absence of troponin showed that HCM-associated mutant Tms did not inhibit as well as wildtype, whereas the DCM associated mutant E40K inhibited better. E54K did not inhibit the actomyosin ATPase activity at any concentration of Tm tested. Thermal denaturation studies by circular dichroism and molecular modeling of the mutations in Tm showed that in general, the DCM mutants caused destabilization within the Tm, while the HCM mutants resulted in increased stability. These findings demonstrate that the structural alterations in Tm observed here may affect the regulatory function of Tm on actin, thereby directly altering the ATPase rates of myosin.